Analisis Yuridis Serta Tindakan BPOM Terhadap Produk Skincare yang Tidak Memiliki Izin BPOM - Bisyri, Thoha; Afifah, Rosalina; Arifah, Refi Aisyah Sakirul; Baihaqi, Ahmad Fahmi Rusdi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The high interest of the Indonesian people in skincare products and the diversity of products and innovations offered by various local and international brands is one of the triggers for the emergence of problems, namely skincare products that are sold without a distribution permit from the Food and Drug Supervisory Agency (BPOM). The purpose of this research is to analyze juridically and the actions taken by BPOM against the buying and selling of skincare products that do not have a BPOM license. The research method used is normative juridical with a statute approach that refers to a number of regulations such as Law No. 17 of 2023, BPOM Regulation No. 21 of 2022, and Law No. 8 of 1999. Skincare products without a BPOM license are considered unlawful and can be subject to criminal and administrative sanctions. BPOM has taken various actions such as surveillance operations, temporary production stoppages, recalls of hazardous products, revocation of distribution permits, and education to the public. The results of this study emphasize the importance of compliance with the rule of law to protect consumers and support the development of a safer and more responsible industry.